Social media perceptions of college football performance and season length 2019–2023 - Michael L. Smith; Austin B. Berenda; Valerie Kilders; Nicole Olynk Widmar; Courtney Bir; F. Bailey Norwood; Zack Neuhofer; Lauren Bales (PLoS ONE, 2025)
College Football carries a strong social, cultural, and economic importance in the United States with teams, universities, the public and others leveraging social media and the online sphere to promote and discuss events and happenings. In our study, we quantify the mentions and underlying public sentiment of online posts related to American College Football originating in the 2019–2023 seasons on social and news media in the United States. We complement this with an analysis of how team performance clustered into conference levels relates to social media data using ordinary least squares. We find the impact of the 2020 season, which had pandemic-induced schedule adjustments, was felt across the sports landscape, but impacted different conferences in diverse ways. We further observe that public sentiment during the season tends to be higher in Power Five conferences that have a lower winning percentage. Additionally, our results suggest that the COVID season corresponds to decreased mentions. The effect on sentiment is less clear, but we more generally find that the winning percentage (positively) predicts sentiment.